2021
DOI: 10.1186/s12870-021-03203-2
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of modulating miR482b level in tomato with botrytis cinerea infection

Abstract: Background Plant miRNAs are involved in the response to biotic and abiotic stresses by altering their expression levels, and they play an important role in the regulation of plant resistance to stress. However, the molecular mechanism that regulates the expression levels of miRNAs in plants with biotic and abiotic stress still needs to be explored. Previously, we found that the expression of the miR482 family was changed in tomato infected by Botrytis cinerea. In this study, we investigated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Notably, pathogenic infections were effectively suppressed in potato [ 31 ], tomato [ 32 ], and cotton [ 33 ] plants through the inhibition of miR482. We found that the expression of stu-miR482a-5p and stu-miR482a-3p was up-regulated with an increase in N application under both types of N stress, which could indicate that miR482a-5p is sensitive to different N treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, pathogenic infections were effectively suppressed in potato [ 31 ], tomato [ 32 ], and cotton [ 33 ] plants through the inhibition of miR482. We found that the expression of stu-miR482a-5p and stu-miR482a-3p was up-regulated with an increase in N application under both types of N stress, which could indicate that miR482a-5p is sensitive to different N treatments.…”
Section: Discussionmentioning
confidence: 99%
“…In wheat, tae-miR171a was validated to have an obvious response to drought memory by regulating the expression of target genes [ 41 ]. The molecular mechanism of miR482b expression in tomato infected by Botrytis cinerea was revealed [ 42 ]. In plants, miR390 is an ancient family of miRNAs and is conserved among species [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroTom / B. cinerea positive [ 101 ] miR482b Tomato cv. MicroTom / B. cinerea negative [ 102 ] miR1127-3p / WRKY75 Tomato ( Solanum lycopersicum cv. Ailsa Craig) / B. cinerea strain B05.10 positive (miRNA repression) [ 30 ] up-regulation of GhmiR395 / APS1/3, adenosine 5′-phosphosulfate; down-regulation of GhmiR165 / REV- transcription factors Cotton ( Gossypium hirsutum L.) / V. dahliae positive [ 103 ] miR398b / NBS-LRR gene and cleavage of the mRNAs of superoxide dismutase and Copper chaperone for superoxide dismutase Cotton ( G. hirsutum cv.…”
Section: Introductionmentioning
confidence: 99%